FRI0559 Knowledge and preferences of patients with knee and hip osteoarthritis (OA) with respect to total joint arthroplasty (TJA). (23rd January 2014) - Suarez-Almazor, M.; Landon, G.; Luo, R.; Singh, J.
Abstract : Background: Significant variations have been described in the utilization of total joint arthroplasty (TJA) in patients with hip and knee osteoarthritis (OA), which cannot be entirely explained by clinical need or heath system issues. Patient preferences may play an important role in this variation. Objectives: To evaluate the knowledge, familiarity and preferences of patients with knee and hip OA with respect to TJA. Methods: Consecutive patients with knee or hip OA attending orthopedic clinics were invited to participate in the study. A survey was administered before the patient's visit with the surgeon inquiring about their preferences for surgery and their familiarity with the procedure. After their visit patients were asked once again about their preferences for surgery. Surgeons were also independently asked whether they had recommended TKA for each patient. Results: 203 patients with knee OA and 78 patients with hip OA were included in the study: 43% were female, 69% white, mean age was 59.6 years. Half of the patients thought they were likely to undergo TKA within the next 6 months. Fifty-three percent of them stated they had little or no knowledge about TKA, and 24% did not know anyone who had undergone TJA. Patients felt that the opinions of their families about surgery were as important as those from their primary care physicians. Patients with hip OA were more likely than those with knee OA to believe that TJA would be very helpful (53% vs. 33% p<0.01), result in significant pain relief (87% vs. 65% p<0.01) and function improvement (85% vs. 65% p=0.03). Risk of complications was felt to be similar by both groups. When asked before the visit about the role they wanted to have at the time of the visit, 28% of the patients wanted their surgeon to make the decision about whether they should undergo TJA, and 22% wanted to make the final decision themselves; however when asked about the role they actually played during visit, the concordance between desired and actual role was low (kappa 0.33). Conclusions: Our results show that patients with OA vary in their knowledge, attitudes and preferences about TJA, suggesting that these may play an important role in the observed variation in the utilization rates for this procedure. Disclosure of Interest: None Declared